Human development is essential to reducing poverty in Ira (Entrepreneurship Journal for Finance and Business, 2026)
Human development is the process of expanding individuals' choices and capabilities, enabling them to achieve better and more productive lives. Human development is essential for poverty reduction, as it helps empower the poor by providing them with the skills, knowledge, and resources needed to improve their lives.Human development helps improve individuals' health by providing healthcare and proper nutrition. This, in turn, leads to increased productivity and reduced medical costs. Human development also contributes to job creation by supporting small and medium-sized enterprises and providing vocational training.Governments, international organizations, and civil society must invest in human development by providing healthcare, education, and vocational training, and by promoting community participation by involving the poor in decision-making that affects their lives. Human development is a powerful tool for poverty reduction. By investing in human development, we can build more just and prosperous societies.